Molecular autopsy by proxy: relevance for genetic counseling in rare genetic disorders - Skrypnyk, Cristina; AlHarmi, Rawan (Frontiers in Genetics, 2024)
Background: Rare genetic disorders may result in death before a definitive clinical diagnosis is established. Aim: This study aims to outline the processes and challenges in managing, from a genetic perspective, couples who lost children affected by rare genetic disorders. Results: Six couples who experienced child loss due to rare genetic disorders, seen by the primary author at genetic evaluation and counseling sessions, were retrospectively analyzed. Four out of 6 couples reported consanguinity. Exome and genome sequencing were performed for the parents. Carrier status of two rare lethal metabolic disorders was confirmed in one consanguineous couple. Three couples were carriers of 3 other rare diseases. Variants of LYST, MPV17, HEXB, ITGB4, CD3E, ASPM, TK2, COL11A2, and LAMB3 genes were identified. Six out of 10 were pathogenic variants, out of which 4 correlated with the demised children's phenotypes. One couple was negative for pathogenic variants. The last couple did not undergo genetic testing since they were beyond the fertile window. Conclusion: Appropriate parental genetic evaluation and counseling are mandatory for selecting the right genetic test to certify the diagnosis postmortem, by virtue of molecular autopsy by proxy. Clarifying a rare disorder diagnosis can help couples to avoid recurrence and plan early for their next pregnancies.